Development of E-Modules Based on Local Wisdom to Improve Students’ Science Literacy and Critical Thinking: A Systematic Literature Review - Gisna Haerani; Dini Sudianti; Muhammad Hendri Diarta (Indonesian Publication Center, 2026)
This study aims to analyze the trends, characteristics, and effectiveness of developing local wisdom-based e-modules in improving students’ scientific literacy and critical thinking skills. The method used was a systematic literature review by examining 15 articles obtained from Google Scholar, ERIC, and DOAJ databases within the 2016–2025 period. The selection process followed the stages of identification, screening, eligibility, and inclusion. Data were analyzed using a descriptive qualitative approach by synthesizing findings based on research methods, study focus, and main results. The findings indicate that most studies employed Research and Development (R&D) and experimental methods. Local wisdom-based e-modules are proven effective in enhancing scientific literacy and critical thinking skills through contextual, interactive, and meaningful learning experiences. The integration of local wisdom makes learning more relevant and increases student engagement. However, most studies still focus on a single aspect of ability and rarely integrate both skills simultaneously. Therefore, further research is needed to develop more innovative and comprehensive e-modules to simultaneously improve scientific literacy and critical thinking skills.